ANALISIS AKTIVITAS ANTIOKSIDAN DAN SITOTOKSIK SENYAWA PELARGONIDIN SEBAGAI KANDIDAT OBAT MENGGUNAKAN METODE DFT (DENSITY FUNCTIONAL THEORY) - Rifno Gusfri Ramadhan; Imelda Imelda; Resin Teja Kusuma; Dwi Syukur Phameswari (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2021)
The antioxidant properties of pelargonidin compounds were studied using the DFT/B3LYP/6-31G method in the gas phase and aqueous solvent. Toxicity analysis was studied using the OSIRIS Property Explorer program. Antioxidant measurement parameters such as BDE, IP, PDE, PA, and ETE values of pelargonidin compounds indicate that the suitable reaction mechanism in the process of radical inhibition by pelargonidin compounds is the SET-PT mechanism because it produces the smallest total energy of IP + PDE. The presence of water in the pelargonidin compound increased the BDE, IP, PDE, PA, and ETE values. Cytotoxic analysis showed that pelargonidin compounds are not mutagenic, do not cause irritation, do not cause tumors, and do not cause interference with the reproductive system. Pelargonidin has a drug score of 0.43 which indicates that pelargonidin is a potential drug candidate.